1999
DOI: 10.2106/00004623-199910000-00032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lengthening Rate on Angiogenesis during Distraction Osteogenesis

Abstract: This study investigated the angiogenic response to four varying rates (0.3,0.7,1.3, and 2.7 d d a y ) of distraction in a rabbit model of leg-lengthening. Immunostaining was performed with use of specific antibodies to type-IV collagen and endothelial cell antigen to examine semiquantitatively the presence of blood vessels in the developing tissues. With use of the Chalkley counting method, the greatest number of positivestaining blood vessel cells was found in the central fibrous zone of the groups that under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(75 citation statements)
references
References 0 publications
4
70
0
1
Order By: Relevance
“…Previously reports using this model have shown that the optimal rate of lengthening is between 0.7 and 1.3 mm, twice daily lengthening [6,7]. However, when lengthened at a higher rate (>1.3 mm/day), the rate of consolidation is decreased, the quality of bone formation is poor and there is a high incidence of soft tissue complications [7,9,17]. In this study, we deliberately chose a fast rate of lengthening (1.4 m d o n c e a day) to mimic clinical situations of poor bone formation during distraction osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously reports using this model have shown that the optimal rate of lengthening is between 0.7 and 1.3 mm, twice daily lengthening [6,7]. However, when lengthened at a higher rate (>1.3 mm/day), the rate of consolidation is decreased, the quality of bone formation is poor and there is a high incidence of soft tissue complications [7,9,17]. In this study, we deliberately chose a fast rate of lengthening (1.4 m d o n c e a day) to mimic clinical situations of poor bone formation during distraction osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Mid-tibia1 osteotomies were performed in 30 adult male NZW rabbits (age 24 weeks, body weight 2.6-3.5 kg; mean 2.68 * 0.26 kg), with the tibiae stabilized with external fixators as previously described [6,7]. After a 7-day latency period, once daily lengthening was initiated at rate of a 1.4 mm/day for 6 days.…”
Section: Anitwul Tnodel Uf Distrucrion Osfeogenesis and Esperimetzru!mentioning
confidence: 99%
“…Bone lengthening using monolateral or circular fixation method is an effective surgical approach in managing difficult orthopedic conditions, such as bone deformity, bone shortening, and bone defects. [1][2][3] Normally, a distraction rate of 0.7-1.3 mm per day was found beneficial for distraction osteogenesis in the rabbit tibial model [4][5][6] and, therefore, a distraction rate of 1 mm per day was adopted and recommended clinically, 7 followed by a sufficient latency period. 8 Complication was, however, reported due to delayed consolidation associated with long sufficient time for neocorticalization and bone maturation 9 and utilization of different lengthening methods.…”
Section: Introductionmentioning
confidence: 99%
“…11 During DO, bone formation occurs in parallel with the tension force, leading to rapid bone formation and remodeling. [2][3][4] The DO technique has been widely used clinically, such as limb reconstruction following bone loss caused by trauma, infection, and tumor resection. 1,2,7,8,11 However, for larger extent lengthening it requires a longer time, as the lengthening rate is around 0.5-1 mm/day and a lengthy period of external fixation is usually needed to allow the newly formed bone to consolidate, during which period complications such as refracture or nonunion of the regenerate at the distraction gap are often seen.…”
Section: Discussionmentioning
confidence: 99%
“…1 During DO, new bone is formed rapidly and is accompanied with advanced angiogenesis and tissue remodeling. [2][3][4] The DO technique has been perfected by Ilizarov and others [5][6][7][8] over the last 2 decades, and it has been widely applied in the managements of bone defects, limb deformities, and fracture nonunions. However, for the management of larger bone defects caused by trauma, bone infection, and bone tumors, the long duration associated with DO treatment and the bone consolidation phase can cause considerable morbidity for the patients, such as refracture, nonunion, infection of pin hole, etc; 7,9-11 and in clinical practice, there is a need for shortening the treatment time of DO and augmentation of bone consolidation during DO.…”
mentioning
confidence: 99%